2016
DOI: 10.1186/s12936-016-1149-1
|View full text |Cite
|
Sign up to set email alerts
|

Status of insecticide resistance in high-risk malaria provinces in Afghanistan

Abstract: BackgroundInsecticide resistance seriously threatens the efficacy of vector control interventions in malaria endemic countries. In Afghanistan, the status of insecticide resistance is largely unknown while distribution of long-lasting insecticidal nets has intensified in recent years. The main objective of this study was thus to measure the level of resistance to four classes of insecticides in provinces with medium to high risk of malaria transmission.MethodsAdult female mosquitoes were reared from larvae suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Moreover it seems that repeated use of pyrethroid insecticides as agricultural pesticides has resulted in a selection pressure on mosquito populations in the study area leading to the development of insecticide resistance. Similar trends have been reported from Middle East different regions, Indian subcontinent, and many African malaria endemic countries [23, 24, 27]. The use of pyrethroids as pesticides in agriculture and bed-net treatment has been recognized as factors responsible for the natural selection of resistant mosquitoes in sub-Saharan Africa [26, 28].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover it seems that repeated use of pyrethroid insecticides as agricultural pesticides has resulted in a selection pressure on mosquito populations in the study area leading to the development of insecticide resistance. Similar trends have been reported from Middle East different regions, Indian subcontinent, and many African malaria endemic countries [23, 24, 27]. The use of pyrethroids as pesticides in agriculture and bed-net treatment has been recognized as factors responsible for the natural selection of resistant mosquitoes in sub-Saharan Africa [26, 28].…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the results of a recent study in Chabahar county in Sistan va Baluchestan Province showed that this species is resistant to lambda-cyhalothrin and tolerant to deltamethrin with mortality rates of 89 and 96 %, respectively [22]. Similar findings have been reported from malaria endemic areas in Afghanistan [23]. Synthetic pyrethroids including deltamethrin and lambda-cyhalothrin are being widely used in various public health programmes to control mosquitoes in many countries.…”
Section: Discussionsupporting
confidence: 59%
“…A study conducted on An. stephensi collected in Afghanistan revealed a low frequency of L1014 wild-type mutation (44%) in mosquitoes and a lack of homozygotes of the mosquitoes that were resistant to deltamethrin (Ahmad et al, 2016). The phenotypic presentation of resistance in the majority of An.…”
Section: Discussionmentioning
confidence: 98%
“…Almost all malaria-endemic countries outside sub-Saharan Africa embraced the GMEP using the main intervention of indoor residual spraying (IRS) [6,7]. Resistance to several insecticides of all major classes has been reported in Anopheles stephensi in other countries of the WHO Eastern Mediterranean Region (EMR), including Saudi Arabia [21,22], Iraq [23,24], Afghanistan [25][26][27][28], and Pakistan [29,30]. Resistance to DDT, dieldrin, malathion, and recently pyrethroid insecticides, was reported from different states of India [31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%